Steam turbine performance under variation of inlet temperature in a steam power plant / Azwin Kamarulzaman - Azwin, Kamarulzaman (2018)
Steam turbine is one of the most important equipment in a power generation plant. With greater demand of power around the globe for domestic and industrial applications, the need on enhancing the power plant performance is substantially emerging. Many researchers scrutinize several parameters such as inlet temperature and pressure, outlet pressure, steam/gas flow rate, geometry, material and economics in efforts to improve the turbine performance. Numerous studies on steam turbines, gas turbines, combined cycle and wind turbines are conducted through simulation, modelling, numerical analysis, theoretical analysis and comparative study. The present work is basically the investigation into the effects of inlet temperature variations on the performance of a steam turbine in a power generation plant through experimental works. The study also intended to measure and analyze the thermodynamics parameters during steam turbine operation and finally validate the factors contributing to the steam turbine performance. The experiment was conducted in a small steam power generation plant of 3 kW capacity. The close cycle system consists of boiler, superheater, steam turbine, condenser, electric generator and pump. Seven different sets of operating parameters are designed and used in this experiment. Other variables namely boiler and turbine pressures, steam flow rate and fuel characteristics are kept as constant to simplify the analysis. The analysis includes determining the thermodynamics and performance parameters involving total heat input, rate of heat input, power output, steam quality, thermal and mechanical efficiencies for the system. Experimental results confirm that high turbine inlet temperature significantly enhances the steam turbine performance in terms of power output, thermal and mechanical efficiencies. Highest mechanical efficiency of 82.85% and power output of 2.485 kWh are obtained when the turbine inlet temperature and pressure are at 148oC and 4 bar respectively with steam quality of 0.9968. Steam quality slightly declines by 0.001% to 0.3% as the turbine inlet temperature escalates. Recommendations for future study are also discussed in this report.